2002
DOI: 10.1172/jci12529
|View full text |Cite
|
Sign up to set email alerts
|

TFF2/SP-deficient mice show decreased gastric proliferation, increased acid secretion, and increased susceptibility to NSAID injury

Abstract: Trefoil factor family 2 (TFF2), also known as spasmolytic polypeptide, is a member of the trefoil family of peptides and is expressed primarily in the mucous neck cells of the gastric mucosa. To study the physiologic role of TFF2, we have generated TFF2-deficient mice through targeted gene disruption. Homozygous mutant mice were viable and fertile without obvious gastrointestinal abnormalities. However, quantitative measurements revealed a significant decrease in gastric mucosal thickness and in gastric mucosa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(45 citation statements)
references
References 50 publications
3
42
0
Order By: Relevance
“…The normal physiological levels of TFF2 could locally reach 10 lM in the gastric lumen [35]. TFF2-deficient mice were more susceptible to gastric ulceration than the normal controls [36]. We speculate that the expression of TFF2 and PAR4 in gastric mucosa and their interaction play an important role in mucosal healing and tissue homeostasis.…”
Section: Discussionmentioning
confidence: 90%
“…The normal physiological levels of TFF2 could locally reach 10 lM in the gastric lumen [35]. TFF2-deficient mice were more susceptible to gastric ulceration than the normal controls [36]. We speculate that the expression of TFF2 and PAR4 in gastric mucosa and their interaction play an important role in mucosal healing and tissue homeostasis.…”
Section: Discussionmentioning
confidence: 90%
“…Mice lacking TFF2 exhibited minor gastric abnormalities, and in contrast to the TFF1 KO these mice had decreased thickness of the gastric mucosa. Furthermore, the mice had increased amounts of gastric acid, and exposure to indomethacin resulted in more severe gastric ulcerations than in wild type mice [155]. Microarray analysis of GI tissues from TFF2 KO mice showed that the majority of the most differentially expressed genes belonged to the immune system, e.g.…”
Section: In Vivo Outcome Of Lacking or Overexpressing Tffsmentioning
confidence: 99%
“…Comparison of the gastric morphology and cellular composition of Car9 −/− and WT littermates was made at corresponding distances from the forestomach. Quantification of total cells and cell subtypes per gastric gland were determined as described before 54. For electron microscopy, samples of the corpus region were rapidly immersed in a fixative solution of 2.5% glutaraldehyde and 1.5% formaldehyde in HEPES buffer, pH 7.3, post‐fixed in OsO 4 and prepared for electron microscopy using a standard protocol 15…”
Section: Methodsmentioning
confidence: 99%